Municipal Wastewater Treatment Technologies in Malaysia: A Short Review - Kristanti, Risky Ayu; Bunrith, Seng; Kumar, Ravinder; Mohamed, Abdelrahim Omar (Tecno Scientifica Publishing, 2023)
The aim of this study was to evaluate different municipal wastewater treatment technologies for commercial use and develop an optimized system for a case study plant and future plant designs. Municipal wastewater, classified as a low-strength waste stream, can be treated using aerobic and anaerobic reactor systems or a combination of both. Aerobic systems are suitable for low-strength wastewaters, while anaerobic systems are suitable for high-strength wastewaters. Malaysia has actively implemented various wastewater treatment technologies to address the increasing demand for clean water and reduce environmental pollution. Some commonly used technologies in Malaysia include Activated Sludge Process (ASP), Membrane Bioreactor (MBR), and Moving Bed Biofilm Reactor (MBBR). These technologies show promise in removing emerging pollutants, such as pharmaceuticals and personal care products, which are not effectively eliminated by conventional treatment methods. Additionally, Malaysia could consider investing in renewable energy sources like solar and wind to power wastewater treatment plants, thereby reducing reliance on non-renewable energy and supporting sustainable development. It is also important to emphasize continued public awareness and education initiatives to promote responsible wastewater disposal practices and environmental stewardship.